Facilitating EFL Learners’ Challenging Writing Learning Enterprises through Self-Regulated Writing Strategy - wijaya, kristian (ELITE JOURNAL, 2024)
ABSTRACT The presented second language writing learning complexities oftentimes hamper globalized EFL learners from accomplishing their targeted writing tasks excellently. Resultantly, their burgeoning writing learning motivation is at high stake and they feel discouraged to proceed into various challenging writing learning dynamics prepared by teachers. One decent response for this general writing learning issue is through the activation of a self-regulated writing strategy. Previous researchers believed that with the accompaniment of a self-regulated writing strategy, EFL learners have become more adept at managing their writing learning processes by employing appropriate writing strategies. Speaking specifically, this present small-scale qualitative library study aimed to review the extent self-regulated writing strategy can facilitate worldwide EFL learners to better cope with arduous writing learning processes. Hence, the researcher conducted an in-depth thematic analysis by reviewing 20 prior self-regulated writing strategy studies in worldwide EFL learning settings to generate more apprehensible and constructive research results. Two major specific themes were stipulated through this data analysis process namely: 1) Self-regulated writing strategy helps EFL learners to become more insightful writers and (2) Self-regulated writing strategy transforms EFL learners into more thoughtful writers. It was evidenced that the employment of a self-regulated writing strategy did not solely transfigure EFL learners into more proficient but also strategic writers. Keywords: Self-regulated writing strategy, EFL learners, library study, thematic analysis